ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.

Specific probe for Hg2+ to delineate even H+ in pure aqueous buffer/Hct116 colon cancer cells: Hg(II)-eta(2)-arene pi-interaction and a TBET-based fluorescence response - Reddy, Upendar G.; Ramu, Vadde; Roy, Sovan; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new molecular probe that demonstrates a distinct TBET process, induced by the Hg(II)-eta(2)-arene pi-interaction, in pure aqueous medium with a large pseudo-Stokes shift of 200 nm.

Cytostatic ruthenium(II)-platinum(II) bis(terpyridyl) anticancer complex that blocks entry into sphase by up-regulating p27(KIP1) - Ramu, Vadde; Gill, Martin R.; Jarman, Paul J.; Turton, David; Thomas, Jim A.; Das, Amitava; Smythe, Carl (Chemistry-A European Journal, 2015)
Cytostatic agents that interfere with specific cellular components to prevent cancer cell growth offer an attractive alternative, or complement, to traditional cytotoxic chemotherapy. Here, we describe the synthesis and characterization of a new binuclear Ru-II-Pt-II complex [Ru(tpy)(tpypma)Pt(Cl)(DMSO)](3+) (tpy=2,2:6,2-terpyridine and tpypma=4-([2,2:6,2-terpyridine]-4-yl)-N-(pyridin-2-ylmethyl)aniline), VR54, which employs the extended terpyridine tpypma ligand to link the two metal centres. In cell-free conditions, VR54 binds DNA by non-intercalative reversible mechanisms (K-b=1.3x10(5)M(-1)) and does not irreversibly bind guanosine. Cellular studies reveal that VR54 suppresses proliferation of A2780 ovarian cancer cells with no cross-resistance in the A2780CIS cisplatin-resistant cell line. Through the preparation of mononuclear Ru-II and Pt-II structural derivatives it was determined that both metal centres are required for this anti-proliferative activity. In stark contrast to cisplatin, VR54 neither activates the DNA-damage response network nor induces significant levels of cell death. Instead, VR54 is cytostatic and inhibits cell proliferation by up-regulating the cyclin-dependent kinase inhibitor p27(KIP1) and inhibiting retinoblastoma protein phosphorylation, which blocks entry into Sphase and results in G1 cell cycle arrest. Thus, VR54 inhibits cancer cell growth by a gain of function at the G1 restriction point. This is the first metal-coordination compound to demonstrate such activity.
Keywords: antitumor agents; cytostatic; p27KIP1; platinum drugs; ruthenium terpyridine

New imaging reagents for lipid dense regions in live cells and the nucleus in fixed MCF-7 cells - Ramu, Vadde; Ali, Firoj; Taye, Nandaraj; Garai, Bikash; Alam, Aftab; Chattopadhyay, Samit; Das, Amitava (Journal of Materials Chemistry B, 2015)
Two new uracil (U) and 5-flurouracil (5-FU) labeled ruthenium(II)-polypyridyl based cellular imaging reagents are reported. Confocal laser scanning microscopic images with live and paraformaldehyde (PFA) fixed MCF-7 cells are examined using these two low-cytotoxic reagents. Experimental results show that these two complexes, appropriately functionalized with U (1) and 5-FU (2), have specific affinity for the lipid dense regions like the endoplasmic reticulum, cell membrane, and cytoplasmic vacuoles in live MCF-7 cells, and dye internalization in these regions happened following an endocytosis pathway. Interestingly, these two complexes are found to be localized in the nucleus of the PFA fixed cells. For fixed cells, presumably the lipid layer disruption helped in the explicit localization of the complexes 1 and 2 in the cell nucleus through specific interaction with cellular DNA. Poor and non-specific internalization of an analogous model complex 3, without having a U or 5-FU moiety, reveals the definite influence of U or 5-FU as well as the role of lipophilicity of the respective complex 1 and 2 in the cellular internalization process. Apart from these, a large Stokes shift (similar to 160 nm) and an appreciably long lived (MLCT)-M-3 excited state (similar to 320 ns) in aq. buffer medium (pH 7.4) are other key features for complexes 1 and 2. Unlike the common nuclear DNA staining reagents like DAPI, these low-cytotoxic reagents are found to be highly stable towards photo-bleaching upon irradiation with 455 nm at the MLCT band for these complexes.

GSH Induced controlled release of levofloxacin from a purpose-built prodrug: luminescence response for probing the drug release in escherichia coli and staphylococcus aureus - Pal, Suman; Ramu, Vadde; Taye, Nandaraj; Mogare, Devraj G.; Yeware, Amar M.; Sarkar, Dhiman; Reddy, D. Srinivasa; Chattopadhyay, Samit; Das, Amitava (Bioconjugate Chemistry, 2016)
Fluoroquinolones are third-generation broad spectrum bactericidal antibiotics and work against both Gram-positive and Gram-negative bacteria. Levofloxacin (L), a fluoroquinolone, is widely used in anti-infective chemotherapy and treatment of urinary tract infection and pneumonia. The main pathogen for urinary tract infections is Escherichia colt, and Streptococcus pneumoniae is responsible for pneumonia, predominantly a lower respiratory tract infection. Poor permeability of L leads to the use of higher dose of this drug and excess drug in the outer cellular fluid leads to central nervous system (CNS) abnormality. One way to counter this is to improve the lipophilicity of the drug molecule, and accordingly, we have synthesized two new Levofloxacin derivatives, which participated in the spatiotemporal release of drug via disulfide bond cleavage induced by glutathione (GSH). Recent studies with Streptococcus mutants suggest that it is localized in epithelial lining fluid (ELF) of the normal lower respiratory tract and the effective [GSH] in ELF is similar to 430 mu M. E. coli typically cause urinary tract infections and the concentration of GSH in porcine bladder epithelium is reported as 0.6 mM for a healthy human. Thus, for the present study we have chosen two important bacteria (Gram + ve and Gram - ve), which are operational in regions having high extracellular GSH concentration. Interestingly, this supports our design of new lipophilic Levofloxacin based prodrugs, which released effective drug on reaction with GSH. Higher lipophilicity favored improved uptake of the prodrugs. Site specific release of the drug (L) could be achieved following a glutathione mediated biochemical transformation process through cleavage of a disulfide bond of these purpose-built prodrugs. Further, appropriate design helped us to demonstrate that it is possible also to control the kinetics of the drug release from respective prodrugs. Associated luminescence enhancement helps in probing the release of the drug from the prodrug in bacteria and helps in elucidating the mechanistic pathway of the transformation. Such an example is scarce in the contemporary literature.

Photo-induced cytotoxicity and anti-metastatic activity of ruthenium(II)-polypyridyl complexes functionalized with tyrosine or tryptophan - Ramu, Vadde; Aute, Sunil; Taye, Nandaraj; Guha, Rweetuparna; Walker, Michael G.; Mogare, Devaraj; Parulekar, Apoorva; Thomas, Jim A.; Chattopadhyay, Samit; Das, Amitava (Dalton Transactions, 2017)
The synergistic effect of oxygen, light, and photosensitizer (PS) has found applications in medicine for the treatment of cancer through photodynamic therapy (PDT). Induction of apoptosis to cancerous cells will prevent tumor metastasis that spreads cancer cells to the neighboring organs/tissues. Herein, we report the two apoptotic Ru(II)-polypyridyl complexes that are functionalized with pendant amino acid moieties tyrosine (1) and tryptophan (2), respectively. These two water soluble complexes were found to interact strongly (K-a(1) = (1.18 +/- 0.28) x 10(5) M-1 and K-a(2) = (1.57 +/- 0.77) x 10(5) M-1) with CT-DNA. Isothermal titration calorimetry (ITC) studies revealed that these complexes bind to CT-DNA through an entropically driven process. Both the complexes showed photo-induced cytotoxicity and exhibit apoptotic activity under photo-irradiation conditions. The comet assay indicated that these complexes can damage cellular DNA, which is attributed to the significant build-up of O-1(2) level even on irradiation with low intensity light (10 J cm(-2), lambda(Range) 450-480 nm). This photoinduced DNA damage and apoptosis in A549 cells was induced by reactive oxygen species (ROS) and occurred through up-regulation of apoptotic marker caspase-3. Control experiments under dark conditions revealed an insignificant cytotoxicity towards these cells for two photosensitive molecules.

Ratiometric sensor for DNA based on a dual emission Ru(dppz) light-switch complex - Walker, Michael G.; Ramu, Vadde; Meijer, Anthony J. H. M.; Das, Amitava; Thomas, Jim A. (Dalton Transactions, 2017)
Herein we describe the DNA binding properties of two new water-soluble ruthenium complexes; experimental and computational data reveal that both complexes display dual emission from MLCT and LLCT excited states. The interaction of the new complexes with DNA was also investigated. Although one of the complexes only binds DNA though groove binding, the second complex has separate ligands capable of groove binding and intercalation. Nevertheless, it was found that both complexes interact with duplex DNA with high affinity. DNA induced distinctive changes in the emission of the complexes; although the groove binding complex only displays a modest increase in emission on binding, the complex that contains the intercalating Ru-II(dppz) moiety displays a large increase in MLCT-based emission on DNA binding while emission from the LLCT excited state is unaffected. This means that the complex functions as the first ratiometric sensor for DNA.